PROPHYLAXIS MECHANISM OF OFFENSES AND CRIME AMONG PUPILS - Zaripov Fayziddin Mukhitdinovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article examines the mechanism of prevention of offenses and crimes among pupils. The article presents the result of the implementation of the improved model developed in the study, aimed at social rehabilitation and social adaptation in order to prevent crime and delinquency of pupils of general education schools: improving the methodology for identifying pupils predisposed to delinquency and crime; carrying out diagnostic and preventive measures among pupils with antisocial behavior, prone to offenses, in cooperation with law enforcement agencies, family, society; provision of legal, social, psychological, medical, pedagogical and other assistance to pupils who have committed offenses; allowed them to determine a set of measures aimed at instilling norms and rules of behavior adopted in society.